Microstructure-controllable low-thermal-conductivity double-phase high-entropy ceramic material and preparation method thereof
By designing a microstructure-controllable low-thermal conduction biphasic high-entropy ceramic material, using the ion ratio and sintering process of different rare earth elements, the problems of insufficient insulation and grain growth of calcined stone-based ceramics at high temperatures are solved, and the problem of insufficient heat insulation and grain growth of calcined stone-based ceramics is achieved. Low thermal conductivity and high temperature stability are used to significantly improve the mechanical properties and structural stability of the material.
Patent Information
- Application Number
- CN202411278166.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
When the calcined stone-based ceramic materials are in service for a long time at high temperatures, the thermal insulation effect is insufficient, and the growth of grains leads to a reduction in thermodynamic performance, and the single-phase structure has problems of sintering or microstructure instability in extreme high temperature environments.
A microstructure controlled low-thermal conductivity biphasic high-entropy ceramic material (YbxRE1yRE2yRE3yRE4y)2B2O7 was designed, and the small-sized calcinedite phase with a large-radius ion partial aggregate is shared with a large-sized fluorite phase with a small-radius ion partial aggregate. It is composed of stable generation and regulation of grain size and distribution ratio through element proportioning and orientation design, and is prepared by dry press forming and high-temperature sintering processes.
Insulation at 1500℃ for 50 hours, the thermal conductivity is lower than 0.8W·m-1·K-1, which significantly inhibits the grain growth rate, improves the strength, toughness and creep resistance of the material, and ensures that Structural stability in high temperature environments.
Smart Images

Figure CN119118661A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high entropy ceramic materials, and in particular relates to a low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure and a preparation method thereof. Background Art
[0002] With the continuous advancement of power plant technology for aircraft engines and marine gas turbines, the operating temperature of their internal high-temperature components has also continued to rise, which has put forward higher requirements on the high-temperature performance of high-temperature component materials, especially surface protective coatings. At present, the thermal barrier coatings applied to the surface of high-temperature components mainly adopt the YSZ (yttria-stabilized zirconia) system. However, when the operating temperature exceeds 1200°C, the performance of the YSZ coating deteriorates due to phase change and high-temperature sintering, making it difficult to meet stringent service requirements. Therefore, the development of new thermal barrier coating materials that can withstand higher temperatures has become a research focus.
[0003] A2B2O7-type pyrochlore-based ceramics have excellent performance in high temperature environments due to their higher melting point and good corrosion resistance. They are considered to be a potential choice to replace traditional YSZ coatings to cope with more severe high temperature environments. In recent years, researchers have conducted extensive research on new pyrochlore-based ceramics through traditional unit / multi-ion doping modification technology. By introducing rare earth ions (Gd, Sm, Y, Eu, Yb, Ce, etc.) of different radii, the lattice structure of the pyrochlore structure is changed by replacing these ions at specific positions in the lattice, thereby optimizing its thermal and mechanical properties. However, when pyrochlore-based ceramic materials serve for a long time at high temperatures, they still face inherent problems such as insufficient thermal insulation effect and reduced thermodynamic properties due to grain growth. The performance of A2B2O7-type pyrochlore-based ceramics still needs to be improved.
[0004] With the introduction of the concept of "high entropy modification" from the field of alloys to the field of ceramic materials, high entropy modified A2B2O7 type pyrochlore-based ceramics has become a research hotspot. The solid solution of five rare earth elements in the pyrochlore lattice triggers a high entropy effect, which further optimizes the thermophysical properties and mechanical properties of ceramic materials. The design concept of multi-principal high entropy alloys provides a high degree of flexibility for the design and optimization of rare earth zirconate materials, but it also makes the controllable generation of ceramic phases a technical challenge. Due to the huge differences in the ionic radius and mass of the five elements, the replacement and diffusion rate of different ions in the lattice structure are difficult to control. And the lack of a corresponding phase diagram makes the generated solid solution phase structure difficult to predict. Therefore, the proposal of high entropy ceramic design principles is of great significance to the development of high entropy ceramic materials.
[0005] Compared with traditional single-component ceramic materials, high-entropy ceramics achieve complex lattice distortion and strong phonon scattering effects by increasing the configuration entropy of the system, thereby effectively reducing thermal conductivity. However, although single-phase high-entropy ceramics have certain advantages in thermal conductivity and high-temperature stability, their single-phase structure still has serious sintering or microstructural instability problems under extreme high temperature environments. In contrast, dual-phase high-entropy ceramics not only provide more flexible microstructural control means by introducing two coexisting phases, but also the dual-phase structure can significantly reduce the diffusion rate and lattice potential energy of ions in high-entropy ceramic materials through the interface effect and synergistic effect between different phases. In order to further improve the service stability of high-entropy ceramics in high-temperature environments, the regulation of ceramic microstructure is also one of the key points of research. The strength of ceramic materials is closely related to the grain size, and reducing the grain size can significantly improve its mechanical properties. In addition, inhibiting the rapid growth of grains at high temperatures is crucial to maintaining the structural stability and thermophysical properties of ceramic materials during service. Summary of the invention
[0006] The purpose of the present invention is to solve the problem that when pyrochlore-based ceramic materials serve for a long time at high temperature, the thermal insulation effect is insufficient and the thermodynamic properties are reduced due to grain growth. A low thermal conductivity dual-phase high-entropy ceramic material with controllable microstructure and a preparation method thereof are provided based on high-entropy ceramic design of configuration entropy, size disorder and mass disorder. The dual-phase high-entropy ceramic has good high-temperature stability and low grain growth rate.
[0007] The chemical formula of the low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure of the present invention is (Yb x RE 1 y RE 2 y RE 3 y RE 4 y )2B2O7, where x = 0.1 to 0.5, x + 4y = 1, RE 1 ,RE 2 ,RE 3 and RE 4 They are four different rare earth elements in the lanthanide series, wherein the lanthanide series contains at least one element whose ion radius is different from that of Yb by more than 6.9%, and the B position is Zr or Hf.
[0008] The microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material of the present invention is composed of small-sized pyrochlore phase (P) grains containing large-radius ion segregation and large-sized fluorite phase (F) grains containing small-radius ion segregation. Through the directional design of element ratio, the stable generation of dual-phase high entropy ceramics is achieved, and the grain size and distribution ratio are regulated.
[0009] The low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure of the present invention does not undergo phase change when kept at 1500°C for 50 hours. The thermal conductivity of the dual-phase high entropy ceramic material is lower than 0.8 W·m at 800-1100°C. -1 ·K -1 .
[0010] The preparation method of the microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material of the present invention is achieved by the following steps:
[0011] Step 1: According to (Yb x RE 1 y RE 2 y RE 3 y RE 4 y )2B2O7 chemical formula Weigh four nano-sized rare earth oxides, Yb2O3 and nano-sized ZrO2 or HfO2 as raw materials;
[0012] Step 2: adding a binder and anhydrous ethanol solvent to the raw materials of step 1, ball milling and mixing, and obtaining a uniform powder after drying;
[0013] Step 3: using a dry pressing process to press the powder obtained in step 2 into a shape to obtain a ceramic green body;
[0014] Step 4: performing high-temperature debinding treatment on the ceramic green body to obtain a debinded ceramic green body;
[0015] Step 5: placing the debinded ceramic embryo in a high-temperature muffle furnace for solid-phase sintering to obtain a low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure.
[0016] The composition design of the low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure of the present invention is achieved through the following calculation principles:
[0017] ① High entropy component element screening principle: RE 1 ,RE 2 ,RE 3 and RE 4 Specifically, they are four different rare earth elements in the lanthanide series, and at least one element having an ion radius different from that of Yb by more than 6.9% is included.
[0018] ② Configuration entropy value of dual-phase high entropy ceramics (S conf ) satisfies S conf >1.50R.
[0019]
[0020] Where: R—air constant (8.314J·K -1·mol -1 ); n—number of element types; X i —i element molar percentage (mol.%).
[0021] ③ The size disorder (δ) of the dual-phase high entropy ceramics satisfies δ>5.29%.
[0022]
[0023] Where: δ—size disorder factor; x i —i is the molar percentage of the element (mol.%); n is the number of element types; r is the number of i —Ionic radius of element i; —The weighted average of the element ionic radii.
[0024] ④ The mass disorder (g) of high entropy ceramics satisfies g>3.8%.
[0025]
[0026] Where: g—mass disorder factor; x i —i is the molar percentage of the element (mol.%); n is the number of element types; m is the number of i — the mass of the i element; —The weighted average of the element masses.
[0027] ⑤ On the basis of satisfying the above conditions, the grain size and distribution ratio are changed by adjusting the size disorder and quality disorder.
[0028] The microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material and the preparation method thereof of the present invention have the following beneficial effects:
[0029] 1. The high entropy ceramic component used in the present invention contains at least one element with a 6.9% difference in ion radius from Yb, which causes the generated high entropy ceramic to produce element segregation, affecting the lattice structure of the ceramic, thereby forming a dual-phase coexistence zone of pyrochlore and fluorite. At high temperatures, it is difficult for the two phases to diffuse and transport materials, so the grain growth in the dual-phase coexistence zone is mutually inhibited, showing a lower growth rate.
[0030] 2. The high disorder design of the present invention expands the size disorder and mass disorder of traditional high entropy pyrochlore-based ceramics, thereby producing a larger lattice distortion. The increase in disorder can effectively break the symmetry inside the material, increase the complexity of lattice vibration, and form a large number of defects, thereby increasing phonon scattering and reducing the phonon mean free path, thereby significantly reducing the thermal conductivity of the ceramic material to 0.8 W·m -1 ·K -1 the following.
[0031] 3. By precisely controlling the ratio of elements, the grain size and distribution inside the material can be controlled, thus forming a dual-phase high-entropy ceramic material with a specific microstructure. This microstructure regulation can not only effectively inhibit the growth of grains under high temperature conditions, but also improve the strength, toughness and creep resistance of the ceramic by optimizing the microstructure of the material, thus providing a guarantee for the stability of the material in high temperature environments.
[0032] 4. The present invention adopts the steps of drying, ball milling, pressing, debinding and high temperature sintering to prepare high entropy ceramics. The rare earth elements are evenly dispersed and fully contacted during the preparation process. The formed two phases reach the solid solution limit, and each phase is a high entropy structure. The method is simple and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 (La prepared in Example 1 of the present invention 0.2 G 0.2 Y 0.2 Sm 0.2 Yb 0.2 )XRD pattern of 2Zr2O7 dual-phase high entropy ceramics;
[0034] Figure 2 (La prepared in Example 1 of the present invention 0.2 G 0.2 Y 0.2 Sm 0.2 Yb 0.2 ) SEM image of the grains of 2Zr2O7 dual-phase high entropy ceramics;
[0035] Figure 3 (La prepared in Example 2 of the present invention 0.175 G 0.175 Y 0.175 Sm 0.175 Yb 0.3 )TEM image of 2Zr2O7 dual-phase high entropy ceramics;
[0036] Figure 4 (La prepared in Example 2 of the present invention 0.175 G 0.175 Y 0.175 Sm 0.175 Yb 0.3 )SEM image of the grains of 2Zr2O7 dual-phase high-entropy ceramics. DETAILED DESCRIPTION
[0037] Specific implementation method 1: The chemical formula of the low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure in this implementation method is (Yb x RE 1 y RE 2y RE 3 y RE 4 y )2B2O7, where x = 0.1 to 0.5, x + 4y = 1, RE 1 ,RE 2 ,RE 3 and RE 4 They are four different rare earth elements in the lanthanide series, wherein the lanthanide series contains at least one element whose ion radius is different from that of Yb by more than 6.9%, and the B position is Zr or Hf.
[0038] Specific embodiment 2: This embodiment is different from the specific embodiment 1 in that the configuration entropy value S of the microstructure controllable low thermal conductivity dual-phase high entropy ceramic material is conf >1.50R.
[0039] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that the size disorder δ of the low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure is greater than 5.29%, and the mass disorder g is greater than 3.8%.
[0040] Specific embodiment 4: The preparation method of the low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure in this embodiment is implemented according to the following steps:
[0041] Step 1: According to (Yb x RE 1 y RE 2 y RE 3 y RE 4 y )2B2O7 chemical formula Weigh four nano-sized rare earth oxides, Yb2O3 and nano-sized ZrO2 or HfO2 as raw materials;
[0042] Step 2: adding a binder and anhydrous ethanol solvent to the raw materials of step 1, ball milling and mixing, and obtaining a uniform powder after drying;
[0043] Step 3: using a dry pressing process to press the powder obtained in step 2 into a shape to obtain a ceramic green body;
[0044] Step 4: performing high-temperature debinding treatment on the ceramic green body to obtain a debinded ceramic green body;
[0045] Step 5: placing the debinded ceramic embryo in a high-temperature muffle furnace for solid-phase sintering to obtain a low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure.
[0046] Specific implementation method five: The difference between this implementation method and specific implementation method four is that in step one, the nano-ZrO2 or HfO2 is pre-dried at a drying temperature of 900°C and a drying time of 6 to 12 hours.
[0047] Specific implementation method 6: This implementation method is different from specific implementation methods 4 or 5 in that the binder described in step 2 is polyvinyl alcohol, methyl amyl alcohol or PVD.
[0048] Specific implementation method 7: This implementation method is different from any one of specific implementation methods 4 to 6 in that in step 2, the mass ratio of the ball milling medium to the raw material is controlled to be 15 to 30:1, the ball milling speed is 300 to 500 rpm / min, and the ball milling time is 24 to 48 hours.
[0049] Specific embodiment eight: This embodiment differs from any one of specific embodiments four to seven in that the drying temperature in step two is 60 to 90° C. and the drying time is 9 to 18 hours.
[0050] Specific embodiment 9: The difference between this embodiment and any one of specific embodiments 4 to 8 is that in step 3, the pressure in the dry pressing process is controlled to be 200 MPa, and the holding time is 15 to 30 minutes.
[0051] Specific embodiment ten: This embodiment is different from any one of specific embodiments four to nine in that the debinding temperature of the high-temperature debinding treatment in step four is 500° C., and the debinding time is 5 to 10 hours.
[0052] Specific implementation eleven: This implementation differs from specific implementations four to ten in that in step five, the temperature of solid phase sintering is controlled to be 1600-1800° C., the sintering time is 24-36 hours, and the heating rate is 10° C. / min.
[0053] Embodiment 1: The preparation method of the low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure in this embodiment is implemented according to the following steps:
[0054] Step 1: Follow (La 0.2 G 0.2 Y 0.2 Sm 0.2 Yb 0.2 )2Zr2O7 chemical formula Weigh La2O3, Gd2O3, Y2O3, Sm2O3, Yb2O3 and nano-sized ZrO2 as raw materials;
[0055] Step 2: Add 2% polyvinyl alcohol by weight to the raw materials of step 1, use anhydrous ethanol as solvent and zirconium oxide balls as ball milling media, configure the ball milling media and the mixed materials in a mass ratio of 20:1, ball mill at a speed of 300 rpm / min for 48 hours, and dry at 90°C for 12 hours to obtain a uniform powder;
[0056] Step 3: using a dry pressing process, the powder obtained in step 2 is pressed at a pressure of 200 MPa for 20 minutes to obtain a ceramic green body;
[0057] Step 4: subjecting the ceramic green body to a high-temperature debinding treatment for 6 hours, controlling the high-temperature debinding temperature to 500° C., to obtain a debinded ceramic green body;
[0058] Step 5: Place the debinded ceramic embryo in a high-temperature muffle furnace for solid-phase sintering at a sintering temperature of 1600°C, a sintering time of 24h, and a heating rate of 10°C / min to obtain a low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure.
[0059] In this embodiment, La, which has a radius difference of 17.76% with Yb, is selected as one of the components, and the other three high entropy ceramic components are Sm, Gd and Y. The element ratio of the prepared dual-phase high entropy ceramic material is designed to obtain a high entropy ceramic (La) with a configuration entropy value of 1.60R, a size disorder degree and a mass disorder degree of 5.61% and 4.28% respectively. 0.2 G 0.2 Y 0.2 Sm 0.2 Yb 0.2 )2Zr2O7.
[0060] Figure 1 The (La prepared in Example 1 is shown 0.2 G 0.2 Y 0.2 Sm 0.2 Yb 0.2 The XRD spectrum of the 2Zr2O7 ceramic sample at room temperature shows that the sample is composed of 43% pyrochlore phase and 57% fluorite phase. The microstructure of the obtained ceramic block was observed by scanning electron microscopy (SEM). Figure 2 As shown in the figure, the obtained ceramic block is composed of small-sized La-rich pyrochlore phase grains and large-sized Yb-rich fluorite phase grains, with an average grain size of 0.89±0.29μm. The obtained dual-phase high-entropy ceramic still maintains good high-temperature phase stability after being exposed to air at 1500℃ for 50h, with a grain growth rate lower than 0.018μm / h, and a thermal conductivity of less than 0.8W·m in the range of 800-1200℃. -1 ·K -1 .
[0061] Embodiment 2: The preparation method of the low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure in this embodiment is implemented according to the following steps:
[0062] Step 1: Follow (La 0.175 G0.175 Y 0.175 Sm 0.175 Yb 0.3 )2Zr2O7 chemical formula Weigh La2O3, Gd2O3, Y2O3, Sm2O3, Yb2O3 and nano-sized ZrO2 as raw materials;
[0063] Step 2: Add 2% polyvinyl alcohol by weight to the raw materials of step 1, use anhydrous ethanol as solvent and zirconium oxide balls as ball milling media, configure the ball milling media and the mixed materials in a mass ratio of 20:1, ball mill at a speed of 300 rpm / min for 48 hours, and dry at 90°C for 12 hours to obtain a uniform powder;
[0064] Step 3: using a dry pressing process, the powder obtained in step 2 is pressed at a pressure of 200 MPa for 20 minutes to obtain a ceramic green body;
[0065] Step 4: subjecting the ceramic green body to a high-temperature debinding treatment for 6 hours, controlling the high-temperature debinding temperature to 500° C., to obtain a debinded ceramic green body;
[0066] Step 5: Place the debinded ceramic embryo in a high-temperature muffle furnace for solid-phase sintering at a sintering temperature of 1600°C, a sintering time of 24h, and a heating rate of 10°C / min to obtain a low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure.
[0067] In this embodiment, La, which has a radius difference of 17.76% with Yb, is selected as one of the components, and the other three high entropy ceramic components are Sm, Gd and Y. The element ratio of the prepared dual-phase high entropy ceramic material is designed to obtain a high entropy ceramic (La) with a configuration entropy value of 1.58R, a size disorder degree and a mass disorder degree of 5.79% and 3.89% respectively. 0.175 G 0.175 Y 0.175 Sm 0.175 Yb 0.3 )2Zr2O7.
[0068] Figure 3 The (La prepared in Example 1 is shown 0.175 G 0.175 Y 0.175 Sm 0.175 Yb 0.3 )2Zr2O7 ceramic sample at room temperature TEM spectrum, after analysis, the sample is composed of pyrochlore phase and fluorite phase. The microstructure of the obtained ceramic block was observed by scanning electron microscopy (SEM), the results are as follows Figure 4As shown in the figure, the obtained ceramic block is composed of small-sized La-rich pyrochlore phase grains and large-sized Yb-rich fluorite phase grains, with an average grain size of 0.82±0.31μm. The obtained dual-phase high-entropy ceramic still maintains good high-temperature phase stability after being exposed to air at 1500℃ for 50h, with a grain growth rate lower than 0.015μm / h, and a thermal conductivity of less than 0.8W·m in the range of 800-1200℃. -1 ·K -1 .
Claims
1. A low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure, Features The chemical formula of the microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material is (Yb x RE 1 y RE 2 y RE 3 y RE 4 y ) 2 B 2 O 7 , where x = 0.1 ~ 0.5, x + 4y = 1, RE 1 ,RE 2 ,RE 3 and RE 4 They are four different rare earth elements in the lanthanide series, wherein the lanthanide series contains at least one element whose ion radius is different from that of Yb by more than 6.9%, and the B position is Zr or Hf.
2. The microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material according to claim 1, Features The configuration entropy value S of the microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material conf >1.50R.
3. The microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material according to claim 1, Features The microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material has a size disorder degree δ>5.29% and a mass disorder degree g>3.8%.
4. The method for preparing the microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material according to claim 1, Features The preparation method is achieved by the following steps: Step 1: According to (Yb x RE 1 y RE 2 y RE 3 y RE 4 y ) 2 B 2 O 7 Chemical formula Weigh four nano-sized rare earth oxides, Yb 2 O 3 and nano-ZrO 2 or HfO 2 As raw materials; Step 2: adding a binder and anhydrous ethanol solvent to the raw materials of step 1, ball milling and mixing, and obtaining a uniform powder after drying; Step 3: using a dry pressing process to press the powder obtained in step 2 into a shape to obtain a ceramic green body; Step 4: performing high-temperature debinding treatment on the ceramic green body to obtain a debinded ceramic green body; Step 5: placing the debinded ceramic embryo in a high-temperature muffle furnace for solid-phase sintering to obtain a low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure.
5. The method for preparing the microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material according to claim 4, Features The binder described in step 2 is polyvinyl alcohol, methyl amyl alcohol or PVD.
6. The method for preparing the microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material according to claim 4, Features In step 2, the mass ratio of the ball milling medium to the raw material is controlled to be 15 to 30:1, the ball milling speed is 300 to 500 rpm / min, and the ball milling time is 24 to 48 hours.
7. The method for preparing the microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material according to claim 4, Features In step 2, the drying temperature is 60-90° C. and the drying time is 9-18 hours.
8. The method for preparing the microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material according to claim 4, Features In step 3, the pressure in the dry pressing process is controlled to be 200 MPa, and the holding time is 15 to 30 minutes.
9. The method for preparing the microstructure-controllable low thermal conductivity dual-phase high entropy ceramic material according to claim 4, Features In step 4, the debinding temperature of the high-temperature debinding treatment is 500° C., and the debinding time is 5 to 10 hours.
10. The method for preparing the low thermal conductivity dual-phase high entropy ceramic material with controllable microstructure according to claim 4, Features In step 5, the temperature of solid phase sintering is controlled to be 1600-1800° C., the sintering time is 24-36 hours, and the heating rate is 10° C. / min.
Citation Information
Patent Citations
High-entropy rare earth zirconate ceramic material for thermal barrier coating and preparation method of high-entropy rare earth zirconate ceramic material
CN117417189A
Cited By
Near-equal-proportion nano double-phase high-entropy zirconate material as well as preparation method and application of near-equal-proportion nano double-phase high-entropy zirconate material
CN119707486A
High-toughness high-entropy zirconate material and preparation method thereof
CN119841637A
A high-toughness, high-entropy zirconate material and its preparation method
CN119841637B
La-doped in-situ coexisting fluorite-perovskite high-entropy zirconate ceramic
CN122916657A
